Utilization of agricultural waste biomass for co-firing fuel for coal-fired power plant with consideration of the potential of slagging, fouling, and abrasion in pulverized coal (PC) boilers - Hariana Hariana; Hanafi Prida Putra; Musthofa Lutfi; Adi Prismantoko (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2022)
The world is moving towards clean energy, especially since the Paris Agreement in 2016. Indonesia is no exception, which must reach 23% of its total energy mix usage from renewable energy sources by 2025, as stated in President Regulation No. 22/2017. Biomass as a renewable energy source can be used as a co-firing fuel for power plants based on its calorific value. This study discusses some of the most important characteristics needed in co-firing fuels, including slagging, fouling, and abrasion, using palm empty fruit bunch (EFB), rice husk (RH), and EFB-RH blended with the composition of 5%, 15%, 25%, and 35% on low-rank coal (LRC) and bituminous coal (BTC). The results showed that the addition of biomass on BTC has no significant effect on the slagging and fouling potential. Conversely, the addition of biomass to LRC significantly reduced the potential of slagging and fouling with the composition of up to 35% biomass which has EFB up to 20%. For blends with 75% of LRC and 25% of biomass blends, only biomass blends with 100% RH can be considered from the aspect of slagging and fouling risk. From potential abrasion characteristics, the addition of biomass on two types of coals did not show any problem for all compositions studied.